Elevated CO2 Concentration and Air Temperature Impacts on Mangrove Plants (Rhizophora apiculata) Under Controlled Environment - Tamimia, Baseem; W. A., Wan Juliana; M.S., Nizam; Mohd Zain, Che Radziah Che (Iraqi Journal of Science, 2019)
Global climate change has shown to have a significant impact on critical ecosystems, that in turn has led to elevated CO2 and temperatures that accompany changes in many abiotic factors, including mangrove forests, facing challenges in their habitat. This study conducted to investigate the morphological and physiological characteristic of the mangrove Rhizophora apiculata in response to elevated CO2 concentration and air temperature for the selection of tree species that are able to adapt to climate change. The seedlings were grown in controlled growth chambers with two temperatures, 21 and 38Â°C, under elevated CO2 at 650 ppm for three months. The plants watered with two liters of saline water of 28 ppt every 48 hours. Thus, after two weeks the mangrove recorded positive results for all parameters to high temperature. The differences in temperature resulted in significant differences and positive interaction between elevated CO2 and decreased temperature that led to the samples survived for all parameters and the growth was very slow, but negative interaction and the samples almost perished under elevated CO2 and increase the temperature for growth and photosynthesis response. These results suggested that the low level of photosynthetic capacity might be attributed to the decreased CO2 fixative reaction system and photosynthetic pigment contents.